2004
DOI: 10.1300/j157v04n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of the Aqueous Extracts of Spicy Food Additives—Evaluation and Comparison with Ascorbic Acid in In Vitro Systems

Abstract: The antioxidant activity of the aqueous extracts of five umbelliferous fruits--caraway (Carum carvi), coriander (Coriandrum sativum), cumin (Cuminum cyminum), dill (Anethum graveolens) and fennel (Foeniculum vulgare)--were investigated in comparison with the known antioxidant ascorbic acid in in vitro studies. The amount of aqueous extract of these five umbelliferous fruits and ascorbic acid needed for 50% scavenging of superoxide radicals was found to be 105 microg (caraway), 370 microg (coriander), 220 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Experimental studies have shown that cumin possesses antimicrobial (Agnihotri & Vaidya, 1996;Singh et al, 2002), anticarcinogenic (Aruna & Sivaramakrishnan, 1992;Gagandeep et al, 2003), antidiabetic (Dhandapani et al, 2002;Sushruta et al, 2006), anti-inflammatory (Srivastava, 1989;Shivakumar et al, 2010), antioxidant (Saito et al, 1976;Huang et al, 1981;Satyanarayana et al, 2004), antinociceptive (Sayyah et al, 2002), antitussive (Boskabady et al, 2006), antiepilepsy (Khatibi et al, 2008), hypocholesterolemic (Shirke & Jagtap, 2009), antifungal (Pai et al, 2010) properties, and improves chick production in poultry industry (Al-Kassi, 2010).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that cumin possesses antimicrobial (Agnihotri & Vaidya, 1996;Singh et al, 2002), anticarcinogenic (Aruna & Sivaramakrishnan, 1992;Gagandeep et al, 2003), antidiabetic (Dhandapani et al, 2002;Sushruta et al, 2006), anti-inflammatory (Srivastava, 1989;Shivakumar et al, 2010), antioxidant (Saito et al, 1976;Huang et al, 1981;Satyanarayana et al, 2004), antinociceptive (Sayyah et al, 2002), antitussive (Boskabady et al, 2006), antiepilepsy (Khatibi et al, 2008), hypocholesterolemic (Shirke & Jagtap, 2009), antifungal (Pai et al, 2010) properties, and improves chick production in poultry industry (Al-Kassi, 2010).…”
Section: Original Articlementioning
confidence: 99%
“…Previously published reports have concluded that the antistress activity of some of the potential medicinal plants could be attributed to their antioxidant effects (Bhattacharya et al, 2001;Satyanarayana et al, 2004;Sreemantula et al, 2005). Based on these reports, the antioxidant activity of cumin extract was also done using in vitro lipid peroxidation assay in brain and liver homogenates of rat.…”
mentioning
confidence: 99%
“…This may be explained by the interaction of the different flavonoids [61] , and/or other compound present in the extracts which are in transition metals [62] . It is reported that the terpenoids and flavonoids having glycosidic linkage are likely to be extracted into aqueous extracts [63] . The compounds containing nitrogen are generally more powerful chelating than phenolic compounds [64] .…”
Section: Aknowledgmentsmentioning
confidence: 99%
“…Antioxidant (Satyanarayana et al 2004) and antibacterial activity of its essential oil (Iacobellis et al 2005;Lixandru et al 2010). Potential anticancer activity in neuroblastoma cell line (Aydin et al 2013).…”
Section: Introductionmentioning
confidence: 99%